Flashbulb memories of the Paris attacks. Issue 3 (25th April 2017) - Gandolphe, Marie‐Charlotte; El Haj, Mohamad
Abstract : Flashbulb memories are vivid autobiographical memories of the circumstances where an individual first learns about emotionally significant public events. Our paper assesses whether these memories were triggered by the attacks of Friday 13 November 2015 in Paris. Two hundred and ninety‐one participants answered a web‐based questionnaire that assessed their memory of the circumstances in which they first learned of the attacks. The questionnaire also assessed vividness, rehearsal, emotion, surprise and novelty. The results showed substantial and vivid recall of the context in which the participants first learned of the event. This recall was associated with fair rehearsal, negative emotional valence, surprise, and novelty. Regression analysis showed that the flashbulb recall was predicted by negative emotion. Negative emotion seems to play a key role in the formation of flashbulb memories, at least those associated with the Paris attacks.